TEACHING ENGLISH BY USING GAME FOR PRIMARY SCHOOL STUDENTS - Vidya Dwi Amalia Zati; Anifah Anifah; Sani Susanti; Elizon Nainggolan (FIP Unimed, 2020)
ABSTRACTIn Indonesia, English begins to be taught in primary school from the first grader by adjusting to children’ ability. Teaching English by using games is one of the best ways to teach children. Games can be used to draw students’ attention to learn English. But, firstly, teachers should consider that a game must has an educational purpose and value, such as Whispering words game, Word family game, Words search game, Board race game, Hot seat game and many mores. The teachers only need to determine the type of games that fits the particular topic of learning and learning purpose. Keywords: Teaching English, Games, Students